2011
DOI: 10.1146/annurev-anchem-061010-113906
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Structure and Composition of Nanoparticles by Extended X-Ray Absorption Fine-Structure Spectroscopy

Abstract: Many metal clusters in the 1-nm size range are catalytically active, and their enhanced reactivity is often attributed to their size, structure, morphology, and details of alloying. Synchrotron sources provide a wide range of opportunities for studying catalysis. Among them, extended X-ray absorption fine-structure (EXAFS) spectroscopy is the premier method for investigating structure and composition of nanocatalysts. In this review, we summarize common methods of EXAFS analysis for geometric and compositional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
162
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 164 publications
(175 citation statements)
references
References 66 publications
13
162
0
Order By: Relevance
“…The reduction in intensity of the NPG can be caused by either the reduced coordination number compared to the bulk, the increased bond length disorder or both. Although it is possible to separately evaluate these two effects in nanoparticles, where the coordination numbers are much smaller than in their bulk counterparts, [36][37][38] in the case of the NPG the discrimination between these two contributions at the single temperature is complicated. Obtaining this information from EXAFS is much easier by utilizing strong temperature dependence of EXAFS amplitude and phase (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The reduction in intensity of the NPG can be caused by either the reduced coordination number compared to the bulk, the increased bond length disorder or both. Although it is possible to separately evaluate these two effects in nanoparticles, where the coordination numbers are much smaller than in their bulk counterparts, [36][37][38] in the case of the NPG the discrimination between these two contributions at the single temperature is complicated. Obtaining this information from EXAFS is much easier by utilizing strong temperature dependence of EXAFS amplitude and phase (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The XANES and extended X-ray absorption fine structure (EXAFS) data processing and analysis were performed using the IFEFFIT package 32 . The EXAFS data modelling and analysis were performed using standard procedures [32][33][34][35][36] .…”
Section: Methodsmentioning
confidence: 99%
“…As the EXAFS signal is averaged over all absorbing atoms, larger Au NPs will not see such a dramatic change in Au-Au coordination with a small change in composition due to the higher amount of atoms in the core versus on the surface. A comprehensive review on the geometrical and compositional characterization of NPs from EXAFS can be found by Frenkel et al [42].…”
Section: Introduction To Gold Nanoclustersmentioning
confidence: 99%